Habitat Preference Modeling of Prehistoric Giant Shark Megalodon During Miocene in Bentang Formation of West Java Coast - Andriwibowo Andriwibowo; Adi Basukriadi; Erwin Nurdin; Muh Aydava Mubarok (UIN Sunan Gunung Djati Bandung, 2021)
In the Miocene era about 20 million years ago, the South Coast of West Java was a sea and habitat for marine organisms including giant sharks Megalodon measuring about 18 meters long. This study aimed to model the habitat preference of the prehistoric gigantic shark Otodus megalodon population based on the fossil record. From fossil teeth, it revealed that the rock layer where the teeth found was Bentang formation from Miocene era. Many fossils of Megalodon had been unearthed from Bentang formation which is part of the South Coast of West Java. The habitat model was developed using the Sea Level Rise Inundation Tool of ArcGIS to estimate the sea depth and Megalodon’s habitat during the Miocene. The length of the teeth of O. megalodon found was ranged from 13 to 19 cm, indicating the presence of juvenile and adult O. megalodon. Based on the model, in the Miocene era, half of West Java was a sea with a depth ranging from 0 to 200 meters. At that time, it was estimated that juvenile O. megalodon occupied waters with a depth of 0-40 meters with an area of 1365 km2. Meanwhile, adult O. megalodon prefers a depth of 80-160 m and the frequency of habitat use increases at a depth of 200 m. The declining population of O. megalodon is associated with climate change and declining prey populations.